The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.4034/1519.0501.2008.0081.0016
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos e Práticas de Pais Quanto à Saúde Bucal e suas Influências Sobre os Cuidados Dispensados aos Filhos

Abstract: RESUMO DESCRIPTORS DESCRITORESResults: Parents/guardians had little knowledge of dental issues; toothbrushing was the most common practice; there was association between the search for pediatric dental assistance and monthly income (p=0.003), education level (p=0.03) and parents/guardians' regular visits to a dental office (p=0.0006). There was also association between assisted toothbrushing to the children and parents/guardians' habit of toothbrushing (p=0.03).No relationship was found among the studied varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 9 publications
0
8
0
12
Order By: Relevance
“…O controle mecânico da placa dentária, mediante escovação associada a agentes químicos e uso regular do fio dental, e a adoção de hábitos alimentares saudáveis, apesar de serem procedimentos relativamente simples e com resultados altamente satisfatórios, ainda não foram alcançados plenamente pela população brasileira (11) . No presente estudo, os pais/responsáveis relataram que a frequência de escovação dental de suas crianças é de três vezes ao dia, corroborando com o relatado em outros trabalhos (12)(13)(14)(15)(16)(17) , e que supervisionam esse procedimento. A frequência da escovação e o acompanhamento dos pais são atitudes muito positivas, no entanto, o IHOS razoável alcançado pelo grupo investigado denota que os procedimentos de remoção da placa dentária efetivados por esses sujeitos ainda não correspondem ao ideal.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O controle mecânico da placa dentária, mediante escovação associada a agentes químicos e uso regular do fio dental, e a adoção de hábitos alimentares saudáveis, apesar de serem procedimentos relativamente simples e com resultados altamente satisfatórios, ainda não foram alcançados plenamente pela população brasileira (11) . No presente estudo, os pais/responsáveis relataram que a frequência de escovação dental de suas crianças é de três vezes ao dia, corroborando com o relatado em outros trabalhos (12)(13)(14)(15)(16)(17) , e que supervisionam esse procedimento. A frequência da escovação e o acompanhamento dos pais são atitudes muito positivas, no entanto, o IHOS razoável alcançado pelo grupo investigado denota que os procedimentos de remoção da placa dentária efetivados por esses sujeitos ainda não correspondem ao ideal.…”
Section: Discussionunclassified
“…O acompanhamento de um adulto, quando da higiene bucal de crianças, é muito importante, pois o adulto, quando bem orientado, poderá explicar e ajudar a criança quanto à técnica correta da escovação dentária e, também, quanto aos cuidados com a deglutição de dentifrício (14,15,22) . Considerando-se o IHOS do grupo avaliado na presente pesquisa, pode-se inferir que os pais/responsáveis que têm supervisionado os procedimentos de higiene bucal dessas crianças não têm o conhecimento correto sobre como efetuar a higienização da cavidade bucal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In spite of the oral hygiene habit being one of the factors directly associated with the development of CPI, children's mothers with CPI in this study presented a superior knowledge to the children's mothers without CPI. This fact can be explained by the knowledge of parents about the determinants of dental caries not being sufficient stimulus for the adoption of care with the children's oral health, reinforcing the idea that there is not necessarily a causal relationship between information and action [18]. Contrary to the findings of the present study, other authors found that the majority of the population studied presented a partial knowledge about care with oral hygiene [9] and classified as a limited knowledge regarding the habits of oral hygiene of parents evaluated, especially in relation to the form of realization of brushing and importance of consultation for the prevention [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is still the place where the basic care with the body takes place and is managed, exercising a fundamental role in health promotion and maintenance of their children [17]. Generally, it is the mother who is responsible for matters involving the health, exercising the function of the educator of knowledge's and habits [18].…”
Section: Discussionmentioning
confidence: 99%